2020
DOI: 10.1530/joe-20-0193
|View full text |Cite
|
Sign up to set email alerts
|

Strength exercise reduces hepatic pyruvate carboxylase and gluconeogenesis in DIO mice

Abstract: Obesity is linked to a reduction in the control of hepatic glucose production, which is the primary mechanism related to fasting hyperglycemia and the development of type 2 diabetes mellitus (T2DM). The main system involved in hepatic gluconeogenesis synthesis is controlled by pyruvate carboxylase (PC), which increases in obesity conditions. Recently, we showed that short-term strength training is an important tool against obesity-induced hyperglycemia. As aerobic exercise can reduce the hepatic PC content of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
1
7
0
1
Order By: Relevance
“…Physical exercise has been another strategy capable of attenuating hepatic glucose production in rodents fed a high-fat diet. This improvement promoted by physical exercise is related to regulating genes and critical proteins of gluconeogenesis such as phospoenolpyruvate carboxykinase and glucose 6-phosphatase (Pauli et al 2014;Pereira et al 2019Pereira et al , 2020Gaspar et al 2020). In our study, the combination of TRF with AE training prevented the increased expression of gluconeogenic genes in diet-induced obesity.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Physical exercise has been another strategy capable of attenuating hepatic glucose production in rodents fed a high-fat diet. This improvement promoted by physical exercise is related to regulating genes and critical proteins of gluconeogenesis such as phospoenolpyruvate carboxykinase and glucose 6-phosphatase (Pauli et al 2014;Pereira et al 2019Pereira et al , 2020Gaspar et al 2020). In our study, the combination of TRF with AE training prevented the increased expression of gluconeogenic genes in diet-induced obesity.…”
Section: Discussionmentioning
confidence: 47%
“…Studies have shown that a high-fat diet negatively affects the metabolic health status, causing changes in the lipid and inflammatory profile, with consequent impairment in insulin sensitivity and glucose homeostasis (McDonald et al 2011;Brunetta et al 2020). Furthermore, previous investigations in the literature have shown that rodents exposed to a high-fat diet developed obesity and hepatic metabolism disturbances, such as increased glucose production and fat accumulation (Cintra et al 2008;Oliveira et al 2015;Pereira et al 2020). In addition, increased body weight has been associated with reduced spontaneous physical activity, further compromising lipid and carbohydrate metabolism in obese rodents (Kohsaka et al 2007;Hatori et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A short-term period of strength exercise resulted in increased hepatic Akt phosphorylation, insulin sensitivity and better glucose homeostasis of the trained group compared to an obese sedentary group. 34 These results were accompanied by an attenuation of hyperglycaemia.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, in the current study, we demonstrated that expression of the gluconeogenic enzyme PCx was significantly decreased by SENP2 disruption, while other enzymes such as PCK1 and G6PC were unaffected. PCx catalyzes the first step of gluconeogenesis and is therefore critical for maintaining glucose metabolic homeostasis (26,27). Kumashiro et al measured the mRNA and protein expression of key gluconeogenic enzymes in human liver specimens and found that only hepatic PCx protein levels correlated strongly with glycemia (26).…”
Section: Discussionmentioning
confidence: 99%